การพัฒนากระบวนการเรียนรู้ทางการศึกษานอกระบบโรงเรียนโดยใช้แนวคิดการเรียนรู้จากการปฏิบัติเพื่อส่งเสริมการปฏิบัติงานของอาสาสมัครสาธารณสุขประจำหมู่บ้าน - ประจวบ แหลมหลัก (จุฬาลงกรณ์มหาวิทยาลัย, 2004)
The purposes of this research were to analyze problems encountered in village health volunteers work performance, to develop a non-formal education learning process based on action learning for enhancing work performance of village health volunteers, and to study problems encountered in learning process implementation. Population in this study was village health volunteers in the 9 provinces of the lower northern region of Thailand. There were 3 steps of this study. For the first step, problem analysis, 400 village health volunteers were selected to indicate their work performance problems from the questionnaires and 5 groups of stakeholders explored their expectations on village health volunteers work performance. For the second step, development of learning process, the problem from the first step was put into learning process from literature review, A group of experts examined the learning process, the learning process was implemented by 40 village health volunteers, and finally the steps of learning process were made a conclusion by the researcher. For the last step, problem analysis of learning process implementation, village health volunteers evaluated the implementation from the questionnaires, from the group of facilitators meeting, and from group discussion of the involved learning process implementation agency. The results of this research were as follows:-1.Village health volunteers indicated that the problem of their work performances was hypertension patient care. The stakeholders expected that village health volunteers had to have hypertension knowledge, to be able to screen and refer patients in their covered area, to produce basic drugs, and to take care of patients. 2.The 8 stages of learning process after putting problem into learning process from literature review and examined by group of experts were preparaton, activities orientation, problem analysis, the cause of problem analysis, determination of alternative solution and decision-making, action planning, plan implementation and results presentation. The researcher, facilitators, and a public health officer had to support village health volunteers to learn in all stages. The results of implementation were that village health volunteers gained hypertension knowledge, developed risk group screening skill and patient caring skill, and screened risk groups in posttest higher than pretest. 3. There were 4 kinds of problems encountered in this learning process implementation including problems of organizers and problems of activities. The problems of organizers were that set advisor couldn t make any clear conclusion, some of group facilitators took less participation, some of village health volunteers dominated others idea, some were busy during learning time, and some wasted time on presentation. The problems of activities were that activities were not related to learners lifestyle. Other problems included limitations of health officers and support of local organization.